O registro em prontuários pelo terapeuta ocupacional em um ambulatório infanto-juvenil - Pelissari, Débora Cristina (2014)
The quality of records conducted on medical record reflects the quality of care provided, and can inform about the health service. The literature raised for this study is emphatic when saying that the record of the professional writing is the only acceptable proof of intervention in treatment. This research is a transversal study, descriptive and exploratory based on technique of documentary analysis. The study aimed to describe what occupational therapists who work in outpatient service are registering in the medical records. For data collection was used a "check-list", which contains information on: Assessment, Intervention and Results. The records analyzed were those of patients who received occupational therapy treatment between June 2012 to June 2013. There were selected only those who were discharged, in order not to bring any bother. 15 medical charts were analyzed. It was found that the initial assessment (93, 3%) was the subtype most frequently used by professionals of the clinic and the method for recording was the use of pre-defined roadmap for the institution (80%), followed by information about the routine, complain and goals of the patient (80%). For intervention records, the subtype record used was the daily evolution (100%), being the narrative (100%) the method used to record the evolutions. Were analyzed 269 records of evolutions. There were found more information about the type of technical procedure used (100%) in the intervention was a free annotation, without a pattern. As for the discharged record it was observed that all professionals use a registry model (100%) as subtype to discharged record and all records (100%) the method used to discharged record was the guide pre- defined by the institution. Information to identify the record and information to identify the patient were the most frequent (93%), followed by information about the intended objectives and if they had been reached or not (26%). The study suggests a closer relationship with the subject rarely discussed in Brazilian literature and may point to a lack of important information in the records, suggesting that this issue needs to be better crafted, stimulating the search for capacity building on the subject. This research also provided knowledge that may guide the practice of occupational therapists, enabling greater accuracy when performing patient records.